Undergraduate athletic training students' influences on career decisions after graduation - Mazerolle, S. M.; Gavin, K. E.; Pitney, W. A.; Casa, D. J.; Burton, L. (Journal of Athletic Training, 2012)
Context: Career opportunities for athletic training students (ATSs) have increased substantially over the past few years. However, ATSs commonly appear to be opting for a more diversified professional experience after graduation. With the diversity in available options, an understanding of career decision is imperative. Objective: To use the theoretical framework of socialization to investigate the influential factors behind the postgraduation decisions of senior ATSs. Design: Qualitative study. Setting: Web-based management system and telephone interviews. Patients or Other Participants: Twenty-two ATSs (16 females, 6 males; age = 22 ± 2 years) who graduated in May 2010 from 13 different programs accredited by the Commission on Accreditation of Athletic Training Education. Data Collection and Analysis: All interviews were transcribed verbatim, and the data were analyzed inductively. Data analysis required independent coding by 2 athletic trainers for specific themes. Credibility of the results was confirmed via peer review, methodologic triangulation, and multiple analyst triangulation. Results: Two higher-order themes emerged from the data analysis: persistence in athletic training (AT) and decision to leave AT. Faculty and clinical instructor support, marketability, and professional growth were supporting themes describing persistence in AT. Shift of interest away from AT, lack of respect for the AT profession, compensation, time commitment, and AT as a stepping stone were themes sustaining the reasons that ATSs leave AT. The aforementioned reasons to leave often were discussed collectively, generating a collective undesirable outlook on the AT profession. Conclusions: Our results highlight the importance of faculty support, professional growth, and early socialization into AT. Socialization of pre-AT students could alter retention rates by providing in-depth information about the profession before students commit in their undergraduate education and by helping reduce attrition before entrance into the workforce.